Migrant penalty in the European labor markets: the interplay between individual characteristics and the regional context - Avola, Maurizio; Piccitto, Giorgio; Vegetti, Federico (Frontiers in Sociology, 2023)
This study aims to verify if and how migrant penalty in the labour market is associated with subnational characteristics, exploring the relevance of the regional occupational structure. We expect that a greater relevance of the share of low-status jobs at the regional level reduces the migrant penalty in terms of the probability of being employed, but increases the gap with natives in terms of job quality.We investigate this trade-off by estimating a set of hierarchical models on the EU-LFS data (2009)(2010)(2011)(2012)(2013)(2014)(2015) for 19 countries and 189 regions. Results suggest a pattern consistent with the trade-off hypothesis, nuanced by heterogeneity at the individual level: in regions where the share of low-status jobs is higher, mid-high educated immigrants from less developed countries are less (or not) penalized compared to natives in terms of employment, while they face a stronger penalty in terms of job quality. What is more, the trade-off is not observed when considering low-educated migrants or those from high-income countries.